Peran Aparatur Desa Dalam Penguatan Kemandirian Dan Pemberdayaan Ekonomi Warga RT.03 RW.02 Desa Semambung, Wonoayu, Sidoarjo: The Role of Village Apparatus in Strengthening Independence and Economic Empowerment of Residents of RT.03 RW.02 Semambung Village, Wonoayu, Sidoarjo - Ibad, Irsyadul; Qomariyah, Nur; Alvi Ariyanti, Sindy Rosita; Anwar, Chairil (Universitas Nahdlatul Ulama Sidoarjo, 2024)
This study aims to analyze the role of village officials in strengthening the independence and economic empowerment of residents of RT.03 RW.02 Semambung Village, Wonoayu District, Sidoarjo Regency. Using qualitative descriptive methods, this study involved interviews with various village officials and direct observation. The results of the study indicate that village officials have played a significant role in supporting programs that encourage the independence and economic empowerment of residents, such as MSME training, innovation development, and BUMDes activities. The RT head plays an active role in providing insight, helping access to capital, and directing business management. The existence of the Night Market and BUMR which are independently managed by residents shows the integration between independence and economic empowerment in practice. Although still facing challenges in participation and coordination, the efforts made show a positive direction in building an independent and economically empowered community. This study concludes that the role of village officials has made an important contribution to strengthening the independence and economic empowerment of residents, but the long-term effectiveness of these efforts still needs to be evaluated and improved sustainably.